2019
DOI: 10.1101/606806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic and metagenomic profiling of hydrocarbon-degrading microorganisms obtained from the deep biosphere of the Gulf of México

Abstract: Marine microbes are capable of degrading hydrocarbons; however, those inhabiting the deep biosphere (>1000 m) remain largely unexplored. Microbial metabolism could lead to the generation of diverse chemistries (some with therapeutic activities), but the impact of using hydrocarbons as the sole source of microbial energy in the synthesis of metabolites, remains obscure. Here, we investigated the metagenomic and metabolomic profile of two deep-marine sediments (>1 200 m deep, designated as A7 and B18) collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…We expected the presence of diverse sequences related to hydrocarbon degradation as previous studies in the water and sediments in the GoM have shown the presence of PHDB (Godoy-Lozano et al, 2018;Moreno-Ulloa et al, 2019;Ramírez et al, 2020). It is important to note that some of the most abundant bacterial genera reported in this work are related to the biodegradation of contaminants and support the idea that microbial communities in deep-sea sediments of GoM have the potential to metabolize a variety of organic compounds, including oil, crude oil and its derivatives.…”
Section: Hydrocarbon Degradation In Sediment and Water Samplessupporting
confidence: 79%
“…We expected the presence of diverse sequences related to hydrocarbon degradation as previous studies in the water and sediments in the GoM have shown the presence of PHDB (Godoy-Lozano et al, 2018;Moreno-Ulloa et al, 2019;Ramírez et al, 2020). It is important to note that some of the most abundant bacterial genera reported in this work are related to the biodegradation of contaminants and support the idea that microbial communities in deep-sea sediments of GoM have the potential to metabolize a variety of organic compounds, including oil, crude oil and its derivatives.…”
Section: Hydrocarbon Degradation In Sediment and Water Samplessupporting
confidence: 79%
“…Notably, the results related to the presence of enzymes involved in oil degradation are consistent with previous works of our own and other groups that investigated the Mexican exclusive economic zone and identified oil-degrading microorganisms derived from 16S amplicon analysis (Fernanda Sánchez-Soto Jiménez et al, 2018;Godoy-Lozano et al, 2018;Hernández-López et al, 2019;Moreno-Ulloa et al, 2019;Raggi et al, 2020;Ramírez et al, 2020); isolated fractions related to petroleum (Moreno-Ulloa et al, 2019); isolated consortia and species capable of degrading petroleum under aerobic and anaerobic conditions (Muriel-Millán et al, 2019;Curiel-Maciel et al, 2021;Rosas-Díaz et al, 2021); and characterized petroleum-degrading enzymes (Rodríguez-Salazar et al, 2020), even in regions with no evidence of anthropogenic perturbation. A recent review illustrated the distribution of bacteria in the water column and sediments of the Mexican exclusive economic zone of the GoM (Rodríguez-Salazar et al, 2021).…”
Section: Identification Of Overrepresented Pathwayssupporting
confidence: 89%
“…Despite that Pseudoalteromonas sp. has a predominant role in hydrocarbon and heavy metal remediation, it is known to efficiently degrade hydrocarbons in association with other bacteria [33,43,44], and from our study co-culturing with Alcanivorax sp. SZN2 does not appear to result in the most efficient complementation.…”
Section: Discussionmentioning
confidence: 58%